Despite stimulus money, most U.S. bridges might stay dumb. - Patel, P. (IEEE spectrum)
The 2.9-kilometer Rion-Antirion Bridge in Greece, with its 300 sensors, is a testament to how smart a piece of infrastructure can be. It routinely tells operators when an earthquake, frequent in those parts, or high winds warrant shutting down traffic.